REGIONAL CLIMATE VARIABILITY FROM RAINFALL AND TEMPERATURE FLUCTUATIONS INSOMALIA - Amir Mohamed Amir (Research Parks Publishers, 2021)
Climate change is accelerating, putting crucial foundations of environmental, social, and economic growth in jeopardy. Climate change signals seem to be very real for many African countries. For several years, Somalia has been one of the countries that has faced unique climate variability and climate change problems duetoan extreme conflict, environmental degradation and a lack of a stable government. The aim of this study was to understand thepattern relationships between rainfall and temperature in past 1901 to 2015 through retrospective study design. The results show that climate variability was experienced t= 56.395, DF=10, P: 0.000, R=.526a, R2=.277, .205, Std.1.00820andF=3.834. Lastly, the study recommended that April and May are the best months for plantingcrops.